A Haunting Strain: An Interpretation of Petrus Lotichius' Elegy 2:4: On the Siege of Magdeburg. Issue 2 (3rd July 2018) - Tipton, Joseph A.
Abstract : This paper offers a new interpretation of the famous elegy written by the Neo-Latin poet Petrus Lotichius on the siege of Magdeburg in 1550–1551, one of the major episodes in the armed conflict between Protestants and the Holy Roman Empire. Taking advantage of recent research on the political doctrine of armed resistance by a lesser magistrate, the paper connects the poem to a treatise composed by Nicolaus Gallus, who defended Magdeburg's decision to rebel against the empire, and argues that the poem's enigmatic rooster, which has defied interpretation for centuries, actually represents Gallus and his justification of Magdeburg's actions. The paper also locates the poem within the larger context of the intra-Lutheran dispute between Philippists and Gnesio-Lutherans and examines the poem's overall meaning as a plea for a balanced appraisal of each other's actions and positions in light of the poet's commitments to both the Protestant and humanist movements.